An updated systematic review of business accelerators: Functions, operation, and gaps in the existing literature - Jaber Aljalahma; Eric John Slof (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
Business accelerators have emerged as an important innovation intermediary, with their primary role identified as stimulating premature startups through mentorship and training programs. However, despite significant improvement and 17 years of working history, there are still gaps in working behavior, business accelerator forms, organizational structure, operations, and outcomes. This systematic review aims to boost the understanding of seed accelerators in innovation and entrepreneurial activities. The Context, Intervention, Mechanism, and Outcome (CIMO) framework was used to collect data from the 53 articles published in the last 17 years. In this current systematic review of applying a CIMO analysis to business accelerators, we retrieved 53 articles for further detailed studies, out of which 21 articles were assessed for the risk of bias analysis. The current review highlights that by providing learning opportunities, idea validation, increased access to growth, and innovation, startup accelerators achieved their goals. Moreover, the study also identified gaps in the literature and opportunities for cohort-based, short-term mentorship programs. The outcomes of the present study will provide suggestions for policymakers, entrepreneurs, managers, and investors.
Keywords: 650; business accelerators; initial startups; innovation accelerators; mechanisms